A comparison of jack-up spudcan penetration predictions and recorded field data. (July 2021) - Hu, Pan; Haghighi, Ali; Coronado, Johan; Leo, Chin; Liyanapathirana, Samanthika; Li, Zheming
Abstract: Installing jack-up spudcan foundations in layered seabed is still challenging in the offshore industry. Before operation, the stability of the jack-up has to be proven by geotechnical analyses. The prediction of leg penetration and possible soil failure (i.e. punch-through or rapid leg run) during the preloading process is of vital importance. This paper reviews 37 offshore sites with 120 penetration records of jack-up unit installations in layered sand-over-clay profiles. For all cases, the preload and the final penetration depth were measured during installation of the spudcan foundations. The properties of the sand and clay soils were determined from site investigation data. This paper presents a modified mechanism-based method to predict penetration resistance for spudcan foundations on sand-over-clay soil profiles. It has been shown that the newly updated method provides a reasonable match to the available field measurements.